Keanekaragaman Jenis Kerang (Pelecypoda) Di Kawasan Hutan Mangrove Desa Katurai Kecamatan Siberut Barat Daya Kabupaten Kepulauan Mentawai - Samalinggai, Benny Gregorius (Pendidikan Biologi, 2014)
Pelecypoda is a natural source of sea which has important economic value and has high diversity. Because of that, the rate of explotation nowadays keep increasing, so that from ecology site can threat Pelecypoda population. The observation result show that mangrove forest condition which is located in Katurai village,South West Siberut, Mentawai Islands district get degradation because the activity which use mangrove forest as the dam so influence to physic-chemistry and biology of mangrove forest and also make a threat of life from various flora and fauna in mangrove forest. The research about various type of cockle shells (Pelecypoda) in mangrove forest has been done in village waterworks and mangrove waterworks in Katurai village,South West Siberut,Mentawai Island district.The sample collection has been done in March to April 2013 by survey method and sample technique with purposive random sampling. In that area, we stated 2 location that village waterworks and mangrove waterworks. In village area is stated three station of sample taking and in mangrove waterworks is stated three stations sample taking. The result can be gotten that the type which is found in that are are G. pecinarum, C. lazarus, Crassostrea sp,. O. angasi, S. glomerata,P. striatum, P. rhomboides, P. puerpora, P. chemnitzi. The highest population of cockle shells are found in mangrove waterworks (12,72 ind/m2) and the lowest are in village waterworks(1,33ind/m2). In village compactness, the highest population is G. pectinarum (0,66 ind/m2) and (KR 50%) in mangrove waterworks is S. glomerata (4,33 ind/m2) and (KR 34,04%). The attendance of shells (%) which is the highest is in location II in mangrove waterworks that is O. angasi with P. bengalensis and in location I of village waterworks is G. pectinarum. The environment which can be measured is still in category that support the pelecpoda.